Humoral innate immunity and the acute phase response 2 - Mantovani, Alberto (Henry Stewart Talks, 2012)
The pentraxin superfamily, The PTX3 pentraxin function in innate immunity and inflammation, Macrophage polarization, Neutrophil extracellular traps
Updated at 2016/08/31